Biomechanical analysis of different osteosyntheses and the combination with bone substitute in tibial head depression fractures. Issue 1 (December 2016) - Jordan, Martin; Zimmermann, Christina; Gho, Sheridan; Frey, Soenke; Blunk, Torsten; Meffert, Rainer; Hoelscher-Doht, Stefanie
Abstract Background Tibial head depression fractures demand a high level of fracture stabilization to prevent a secondary loss of reduction after surgery. Elderly individuals are at an increased risk of developing these fractures, and biomechanical investigations of the fractures are rare. Therefore, the aim of this study was to systematically analyze different types of osteosyntheses in combination with two commonly used bone substitutes. Methods Lateral tibial head depression fractures were created in synthetic bones. After reduction, the fractures were stabilized with eight different treatment options of osteosynthesis alone or in combination with a bone substitute. Two screws, 4 screws and a lateral buttress plate were investigated. As a bone substitute, two common clinically used calcium phosphate cements, Norian® Drillable and ChronOS™ Inject, were applied. Displacement of the articular fracture fragment (mm) during cyclic loading, stiffness (N/mm) and maximum load (N) in Load-to-Failure tests were measured. Results The three different osteosyntheses (Group 1: 2 screws, group 2: 4 screws, group 3: plate) alone revealed a significantly higher displacement compared to the control group (Group 7: ChronOS™ Inject only) (Group 1, 7 [p  < 0.01]; group 2, 7 [p  = 0.04]; group 3, 7 [p  < 0.01]). However, the osteosyntheses in combination with bone substitute exhibited no differences in displacement compared to the control group. The buttress plate demonstrated a higher normalized maximum load than the 2 and 4 screw osteosynthesis. Comparing the two different bone substitutes to each other, ChronOS™ inject had a significantly higher stiffness and lower displacement than Norian® Drillable. Conclusions The highest biomechanical stability under maximal loading was provided by a buttress plate osteosynthesis. A bone substitute, such as the biomechanically favorable ChronOS™ Inject, is essential to reduce the displacement under lower loading.